Noise baseline data for Ninoy Aquino Parks and Wildlife Nature Center a protected area - Mendoza, Victorino C. (1997)
Ninoy Aquino Parks and Wildlife Nature Center (NAPWNC) is one of the Protected Areas (PA) considered as an initial component under the existing Republic Act 7586 known as the National Integrated Protected Areas System (NIPAS) Act of 1992. Currently, NAPWNC is considered an area of national significance which is characterized by harmonious interaction of man and nature while providing opportunities for public enjoyment through recreation and tourism. In order to continue enhancing the quality of service to the visiting public, one of the intentions of this study is to help the administration of NAPWNC in the management of the said park through proper sectoring and zoning for a better and functional use as far as environmental noise and related cotrol measures are concerned. Under the existing Department of Environment and Natural Resources (DENR) Environmental Quality Standard for Noise in General Areas, NAPWNC - PA is not yet specifically classified.